Potensi Perkembangan Asuransi Syariah di Indonesia - Safira, Miftah Hanny; Nasrullah, Muhammad Ginga; Aulia, Yasina Fatimah (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2021)
Indonesia is one of countries that have largest Muslim population. The potential and opportunity for Islamic finance in Indonesiaa therefore is huge including Islamic insurance sector. This article aims to identify and analyse the potential development of the Islamic insurance market in Indonesia. By using systematic literature review which uses books and other related literature, the result shows that the potential development of Islamic insurance in Indonesia is already large. This is proven by the existence of several supporting factors and also strategies which is directed to develop Islamic insurance especially from government that making official regulation.